Fede e scienza si coniugano insieme: armonia e collaborazione tra scienza e fede alla luce dell’enciclica Fides et ratio - Aguilar LC, Alfonso (Alpha Omega, 2010)
Although scattered throughout the document, John Paul II’s encyclical Fides et ratio offers us thoughtful insights about the relationship between faith and science. In the first place, the tragic consequences of the current clash between science and faith are highlighted. The Biblical foundation of the harmony that must reign between these two forms of knowledge is explained. In order to be harmonious and beneficial, the relationship between faith and science must be that of cooperation in the mutual respect of each other’s relative autonomy. Wrong forms of relationship are rejected. Finally, the encyclical outines some of the benefits that must come from the unity between science and faith.